Keluaran 6:1-6 sebagai Paradigma Teologi Penebusan dalam Perjanjian Lama - Bonnarty Steven Silalahi (Predica Verbum: Jurnal Teologi dan Misi, 2025)
This study examines the paradigm of redemption theology in the Old Testament based on an exegetical analysis of Exodus 6:1-6. The study demonstrates that the transition from El Shaddai to YHWH is not merely a linguistic shift but part of God's progressive revelation in Israel’s salvation history. The findings reveal that redemption in the Old Testament encompasses two key aspects. First, redemption as a historical act, where God not only made promises to Israel's ancestors but also actively intervened to liberate them from Egyptian bondage. This is reflected in the use of the verb וְגָאַלְתִּי (wegā’altî, ‘I will redeem’), emphasizing that God acts as Go’el (Redeemer), who not only delivers Israel but also claims them as His own. Second, redemption as a covenantal relationship, where divine liberation is not merely a political or social action but a restoration of the covenantal bond between God and His people. The phrase וְלָקַחְתִּי אֶתְכֶם לִי לְעָם (welāqakhtî ʼetkem lî leʻām, ‘I will take you to be My people’) affirms that God’s redemption is always linked to the restoration of His people’s identity as a covenant nation. Thus, this study concludes that salvation in the Old Testament is not only about deliverance from slavery but also about the covenantal bond rooted in God’s grace.